The linguistic and cultural aspect of numerological phraseologies and phraseologies based on the organs of the human body (Multidisciplinary Journal of Science and Technology, 2026)
This article offers a comparative analysis of the linguistic and cultural aspects of numerological phraseology and phraseological units formed from the names of human body parts in French and Uzbek. The study interprets these phraseological units as an important linguistic phenomenon, reflecting national thought, cultural values, historical memory, and the worldview of these peoples. The article reveals the semantic and symbolic properties of expressions involving numbers (one, two, three, seven, forty) and analyzes their place in French and Uzbek cultures. The expression of emotional, moral, and cognitive concepts in both languages is also illustrated by the example of phraseological units relating to body parts such as the heart (cœur / kö'ngıl), the head (tête / baş), the eye (yeux / ko'z), and the hand (main / köl). The results of the comparative analysis show that in French, logic and rationality prevail, while in Uzbek, spirituality, symbolism, and moral evaluation are predominant. This study constitutes an important scientific resource for the study of phraseology from a linguocultural perspective, as well as for a better understanding of the national and cultural characteristics of the French and Uzbek languages.